Pengaruh Gamifikasi Tantangan Misi (TaMis) terhadap Kemampuan Berpikir Aljabar pada Mata Pelajaran Matematika Materi Pola Gambar dan Pola Bilangan di Kelas IV SDN 19 Cakranegara - Shakila; Radiusman; Ibrahim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the effect of the "Mission Challenge" (TAMIS) gamification on algebraic thinking skills regarding the topics of visual and numerical patterns in the fourth-grade mathematics curriculum at SDN 19 Cakranegara. The study was motivated by the students' low algebraic thinking skills in these subject areas. A quantitative approach was employed using a quasi-experimental design specifically, the Nonequivalent Control Group Design. The sample was selected via purposive sampling, comprising 26 students from class IV-B (experimental group) and 29 students from class IV-A (control group). Data collection techniques included testing, observation, and documentation. Research instruments consisted of eight essay questions assessing algebraic thinking skills, an observation sheet for lesson implementation, and documentation. Data analysis involved normality testing (Shapiro-Wilk) and homogeneity testing (Levene’s Test). Hypothesis testing was conducted using the Independent Sample t-Test. The analysis results indicated that the data were normally distributed and homogeneous. The hypothesis test yielded a significance value (2-tailed) of 0.017 (< 0.05); consequently, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. Thus, it can be concluded that the use of the "Mission Challenge" (TAMIS) gamification has a significant effect on students' algebraic thinking skills regarding visual and numerical patterns in the fourth grade at SDN 19 Cakranegara.